Development of robust isothermal RNA amplification assay for lab-free testing of RNA viruses - Radhika Biyani; Kirti Sharma; Kenji Kojima; Madhu Biyani; Vishnu Sharma; Tarun Kumawat; Kevin Maafu Juma; Itaru Yanagihara; Shinsuke Fujiwara; Eiichi Kodama; Yuzuru Takamura; Masahiro Takagi; et al. (Scientific Reports, 2021)
Abstract Simple tests of infectiousness that return results in minutes and directly from samples even with low viral loads could be a potential game-changer in the fight against COVID-19. Here, we describe an improved isothermal nucleic acid amplification assay, termed the RICCA (RNA Isothermal Co-assisted and Coupled Amplification) reaction, that consists of a simple one-pot format of ‘sample-in and result-out’ with a primary focus on the detection of low copy numbers of RNA virus directly from saliva without the need for laboratory processing. We demonstrate our assay by detecting 16S rRNA directly from E. coli cells with a sensitivity as low as 8 CFU/μL and RNA fragments from a synthetic template of SARS-CoV-2 with a sensitivity as low as 1740 copies/μL. We further demonstrate the applicability of our assay for real-time testing at the point of care by designing a closed format for paper-based lateral flow assay and detecting heat-inactivated SARS-COV-2 virus in human saliva at concentrations ranging from 28,000 to 2.8 copies/μL with a total assay time of 15–30 min.